Analysis of Correspondence Reviews Texts and Stars Ratings (Моделювання, керування та інформаційні технології, 2020)
The article analyses the connection between the clients’ reviews of the texts and their published  ratings. To realize the task the language R and the packages such as jsonlite, tm, SnowballC, wordcloud, RColorBrewer, ggplot2 and others have been chosen. We used the data of the service Yelp, opened for academic goals and analysis [6]. For the analysis we used sentiment analysis. Sentiment analysis is the computational treatment of opinions, sentiments and subjectivity of text.